Pterospermum truncatolobatum Gagnepain (Sterculaceae): A new addition to the flora of Nepal - Basnet, B. K.; Siwakoti, M. (Banko Janakari, 2018)
Not available. Banko Janakari A Journal of Forestry Information for Nepal Vol. 28, No. 1, 2018, page: 48-49